Development and Validation of a Work-Family Enrichment Model: Insights from Thai Family Enterprises - Apisakkul, Akachai; Chirapanda , Suthawan (Journal of Ecohumanism, 2024)
The objectives of this study were to 1) develop a Work-Family Enrichment model for family businesses and 2) examine the consistency of the developed model with empirical data. The sample group consisted of 207 family members of family business owners in Thailand. Data were collected using the Work-Family Enrichment assessment. The model was found to be consistent with empirical data, supporting the hypothesis. These findings emphasize the importance of balancing work and family roles to improve both organizational outcomes and family well-being in family-run enterprises.